De fremmede, Det Gamle Testamente, vi - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 1987)
On the basis of examples of attitudes towards foreigners in the Old Testament, the internal tension between a tendency to eliminate the differences between Israel and foreigners and an insistence on maintaining the fundamental distance between Israel and foreigners, even in eschatological perspective, is presented. The a priori assumption of the Israelitic understanding of themselves is not a differentiation between nature and culture (between non-human and the human), but between the human in general and the specifically Israelitic. This difference cannot be transgressed without the break-down of the Israelitic system. Identity is understood here as establishing differences. But the dialectic between the Old Testament beginnings which are negated by the history of Israel, continues in the New Testament which negates the history of Israel and yet which allows the Old Testament to remain as an equal part of the canon. The practical universalism (modernism) of the Western world and the eradication of ethnic differences is thereby partly anticipated as a problematic in the Christian canon and partly given an important corrective.